Application of Task-Based Learning in Teaching Business Chinese Reading in Thailand - Ping, Xu (Scholar: Human Sciences, 2015)
Task-Based Learning (TBL) has been attracting the attention of researchers and language teachers for many years. However, far less research has been carried out as to whether TBL works for teaching Business Chinese Reading. This study aims to offer a unique contribution by integrating a discussion of TBL pedagogical principles with descriptions of their application to teaching Business Chinese Reading. This study uses the basic principles and main ideas of TBL as the foundation and combines the specific characteristics of Business Chinese Reading. Integrating both quantitative and qualitative approaches, this study examines the knowledge and application of TBL among Assumption University students who study Chinese as a second language. To testify TBL is more effective than traditional teacher-center instruction, an experimental study is carried out in the research. The research subjects consisted of 54 senior students in Business Chinese Department of Assumption University. Students in both experimental group and control group received a pretest during the week before instruction began, and they also received a post-test during the week after instruction concluded. From the analysis it is easy to get the conclusion that TBL used appropriately in teaching Business Chinese Reading is helpful in improving students‘ reading skills.